Organizing a Wartime Shipyard: The Union Struggle for a Closed Shop at West Coast Shipbuilders Limited 1941–44 - Madsen, Chris (Labour / Le Travail, 2010)
Abstract During World War II thousands of workers entered the employ of wartime shipyards in British Columbia. Most Vancouver-area shipyards, following general practice in the United States along the Pacific Coast, operated on the basis of a closed shop, whereby membership was required in recognized labour unions holding agreements with the companies. Management at one shipyard, West Coast Shipbuilders Company Limited, however, bucked this trend and maintained an open shop in the face of growing pressure by the unions, in particular the marine boilermakers, to have a closed one. William McLaren, the main antagonist, reflected enduring older values among some employers in antithesis to labour-management cooperation prevalent in the United States and Canada in support of war production. Though the matter went to conciliation, the drawbacks of a legal approach were readily apparent when a board turned down labour’s request, and negotiations assisted by a judge resulted in adoption of a lesser maintenance of membership clause instead of the closed shop. Worker militancy and aggressive organizing, in the end, could not deliver the closed shop at West Coast Shipbuilders before war contracts concluded and shipbuilding contracted in the province. Taking a local, regional, and industry-specific perspective, this study argues that the union struggle for recognition and accommodation from employers in wartime Canada faltered in the case of obtaining a closed shop at this British Columbia wartime shipyard.